Linkages Between Financial Variables, Financial Sector Reform and Economic Growth and Efficiency - Johnston, R. (IMF Working Papers; Working Paper, 1995)
This paper analyzes the different channels through which financial variables and financial sector reform can affect economic growth and efficiency, using panel data for 40 countries which reformed their financial systems. Financial sector reform is hypothesized to affect economic growth and efficiency through three main channels: the real interest rate representing the interest cost of capital, the volume of intermediation, and financial sector efficiency. The results indicate that financial reforms have structural effects; that financial variables and reforms are important determinants of economic performance; that the impact depends on whether countries did or did not face a financial crisis; and that the 'quality' of financial sector reform matters.